Sea Turtle Identification and Viewing Guidelines - Lindsay Nester; William M. Giuliano (EDIS)
WEC-209, a 4-page illustrated fact sheet by Lindsay Nester and William M. Giuliano, provides instruction in how to appropriately view threatened and endangered sea turtles nesting and hatching; how to deal with stranded, injured, or dead turtles; and how to identify leatherback, green, loggerhead, hawksbill, and Kemps ridley turtles. Includes contact information for the Florida Wildlife Commission Hotline and how to find a turtle watch program in Florida. First published: May 2006.